Overcoming barriers to prostate cancer care in the Philippines - Vergara, Thomas Vincent; Magsanoc, Juan Martin; Mendoza, Marvin Jonne; Cornelio, Gerardo Tomas; De Guzman, Rudolfo; Magsanoc, Nikko; Serrano, Dennis (Frontiers in Urology, 2024)
Prostate cancer (PCa) is a health concern affecting millions of men globally, with a concerning rise in incidence in the Philippines, a country that faces a complex set of barriers to equitable access to quality PCa care. In this article, we describe the unique geographic, economic, socio-cultural, and political factors that influence access to screening, diagnosis, treatment, and supportive services in the country, and explore avenues for development.The country lacks a nationwide PCa registry to inform resource allocation and guide PCa cancer care programs and policy. Misconceptions, cultural barriers and negative attitudes about PCa among Filipino men adversely influence health-seeking behavior. Inadequate insurance coverage, and high out-of-pocket costs obstruct access to essential care. Geographic and political factors contribute to the uneven distribution of healthcare resources needed for comprehensive PCa care, including access to medical specialists, essential medicines, and surgical and radiotherapeutic equipment.Overcoming these challenges requires a collaborative effort encompassing robust data collection, awareness campaigns to reshape societal norms, policy and economic reforms, infrastructure improvements, and enhanced collaboration among healthcare professionals to provide evidencebased care. Addressing these issues holistically can pave the way to better outcomes and improved quality of life for Filipino men with this life-altering disease.